Haematology, serum biochemistry and organ weight changes of wistar rats fed processed dehulled jack bean (canavalia ensiformis) (2015)
A total of fifty Wistar albino rats weighing 50-60g were randomly allocated to five dietary : treatments in a completely randomized design ,to investigate the haematology, serum biochemistry and organ weight changes on diets containing processed dehulled jack bean. Four diets containing 10% crude protein were formulated to contain casein (Tl)-control diet dehulled jack bean soaked in filtrate obtained from 24hr water-steeped whole maize grains (T2), dehulled jack bean soaked in lye solution (T3), dehulled jack bean boiled or 15 minutes (T4) while a protein free diet served as a negative control (T5). The feeding trial lasted for 28days after which four rats per treatments were sampled to evaluate haematological and serum biochemical indices while three rats per treatment were sacrificed by cervical decapitation and the heart, liver, kidneys and the lungs removed and weighed separately. Haemoglobin (Hb), white blood cells (WBC), eosinophil and Mean Corpuscular Haemoglobin Concentration (MCHC) were not affected by dietary treatments while the packed cell volume, red blood cells, lymphocytes, neutrophils, monocytes, Mean Corpuscular Volume (MCV) and Mean Corpuscular Haemoglobin (MCH) were significantly affected (P<0.05) by dietary treatments. Rats on T4 had the highest PCV (47.00%), and neutrophil (25.67%) values, while rat on control had the highest value ofRBC 5.95 (10(6)/mm3). Rats on T2 had the highest lymphocyte (80.33%) and monocyte (3.50%) values, while the lowest value was for rats T4 (73.25%) and T3 (2.00%). Rats on T3 had the highest MCV (1.57fl) and MCH (0.40pg) values the total protein and alkaline phosphatise (ALP) were similar (P>0.05) for all group, while the albumin, globulin, cholesterol, Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) were influence by dietary treatments (P<0.05). Albumin values ranges from 5.83g/dl to 7.68g/dl with rats on T4 having the highest albumin value (7.63g/dl). Globulin value for rats onT4 is significantly (P<0.05) different from rats on TI, T2, T3, and T5 with rats on T3 having the highest value (3.42). Rats on TI had the highest Cholesterol (55.37mg/dl) and ALT (17.49IU/L) value, while Rats on T2 had the highest AST (16.13IU/L) value. Kidney weights were similar for all group (P>0.05) while the liver, lungs and heart relative weights were significantly affected (P< 0.05) by dietary treatments. Rats on control diet had the lowest relative weight for liver (3.74), lungs (1.03), kidney (0.92) and heart (0.49). Rats on T3 and T5 had the highest value for heart weight (0.75) and liver weight (5.67) while rats on T4 had the highest value for lungs (1.59). Rats fed dehulled jack bean seed soaked in ogi liquor showed slight improvement on haematological, serum profile and organ weight changes over those fed lye soaked jack bean and boiled for 15minutes. However, all the processing methods were ineffective when compared to the performance of rat fed casein based diets.